Uji diagnostik skor apgar pada asfiksia neonatorum - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRAK Diagnostic test of Apgar score for neonatal asphyxia Background: Neonatal asphyxia is one of the leading causes of neonatal mortality. Nowadays there are many controversies regarding the accuracy of Apgar score. Objective: The objective of this study was to know the diagnostic value of Apgar score to diagnose neonatal asphyxia. Methods: This study was carried out in Division of Perinatology, Department of Child Health, Faculty of Medicine/Dr. Sardjito Hospital. The subjects were all living newborns. Newborns with congenital defect, gestational age 5 28 weeks, and birth weight less than 1,000 grams were excluded. Apgar Score was performed by trained doctors in Perinatology Sub Division at five minutes. The classification of asphyxia according to blood gas analysis is: no asphyxia (pH 7.105), mild asphyxia (pH 7.003 - < 7.105), severe asphyxia (pH